2009
DOI: 10.1186/2047-783x-14-s4-21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking and body weight on adipokines in middle aged women

Abstract: ObjectiveQuitting smoking was associated with an undesirable weight gain. Both, cigarette smoking and obesity were accompanied by subclinical systemic inflammation. This may cause unfavourable changes in (plasma) adipokine concentration. The aim of the present study was to establish the influence of moderate cigarette smoking on the concentration of the adipokines leptin and adiponectin and the pro-inflammatory factors CRP, SAA, IL-6 and TNF-α in non-obese (n = 138) and obese (n = 175) perimenopausal women of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Consequently, in the comparison between the macrosomic and non‐macrosomic groups, the levels in maternal serum must be adjusted for these maternal characteristics. These findings are compatible with results of previous studies in non‐pregnant individuals, which reported a poor adipocytokine profile in women of African and South Asian racial origin (Meilleur et al , 2010; Mente et al , 2010) and in cigarette smokers (Swarbrick and Havel, 2008; Bergmann and Siekmeier, 2009). Similarly, studies in pregnancy have also shown decreased adiponectin levels with smoking and in women of African, South Asian and East Asian racial origin (Retnakaran et al , 2004; Nien et al , 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, in the comparison between the macrosomic and non‐macrosomic groups, the levels in maternal serum must be adjusted for these maternal characteristics. These findings are compatible with results of previous studies in non‐pregnant individuals, which reported a poor adipocytokine profile in women of African and South Asian racial origin (Meilleur et al , 2010; Mente et al , 2010) and in cigarette smokers (Swarbrick and Havel, 2008; Bergmann and Siekmeier, 2009). Similarly, studies in pregnancy have also shown decreased adiponectin levels with smoking and in women of African, South Asian and East Asian racial origin (Retnakaran et al , 2004; Nien et al , 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In normal-weight women, smoking has a deleterious effect on adiponectin circulating levels which is in accordance to previous data [ 25 ]. However, this is not observed in the obese group, perhaps because the prevalence of smokers is far less than in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The relevance of this finding is not straight forward as also relatively trivial inflammatory stimuli can lead to rapid SAA responses [23]. Nevertheless our findings are at odds with previous reports [24,25] showing higher level of SAA in smokers, for which we have no explanation.…”
Section: Discussioncontrasting
confidence: 82%